2022
DOI: 10.3389/fcvm.2022.905607
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prasugrel and Ticagrelor on Platelet Reactivity in Patients With Acute Coronary Syndrome: A Meta-Analysis

Abstract: BackgroundThis meta-analysis mainly aimed to compare the impact of prasugrel and ticagrelor on platelet reactivity (PR) in patients with acute coronary syndrome (ACS).MethodsWe searched four electronic databases to identify randomized controlled trials and cohort studies comparing the impact of prasugrel and ticagrelor on PR in patients with ACS. We performed group analyses according to three detection methods, drug dose [loading dose (LD) and maintenance dose (MTD)] and LD effect time, and assessed the robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
1
0
1
Order By: Relevance
“…[ 50 51 52 ] Four meta-analyses have shown that HTPR is lower with ticagrelor compared to prasugrel. [ 53 54 55 56 ] However, some studies suggest the variation is due to the type of PFT assay used rather than the effect of the drug per se. [ 57 58 59 ] However, the small SWAP-3 trial demonstrated that switching to ticagrelor from prasugrel leads to further platelet inhibition and lower PRU as early as 2 h after drug initiation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 50 51 52 ] Four meta-analyses have shown that HTPR is lower with ticagrelor compared to prasugrel. [ 53 54 55 56 ] However, some studies suggest the variation is due to the type of PFT assay used rather than the effect of the drug per se. [ 57 58 59 ] However, the small SWAP-3 trial demonstrated that switching to ticagrelor from prasugrel leads to further platelet inhibition and lower PRU as early as 2 h after drug initiation.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the range of ticagrelor HTPR after loading dose administration ranged from 1.5 to 60.2%, depending on studied patient population, method used for HTPR detection and timing of blood sampling [ 50 , 51 , 63 , 64 , 65 , 66 , 67 ]. Although Verdoia et al reported in their studies [ 54 , 68 , 69 ] 8.6 to 13.7% prevalence of ticagrelor HTPR on maintenance dosing (tested 30 to 90 days post drug loading), it seems that a longer duration of ticagrelor therapy probably achieves sufficient platelet inhibition in the majority of patients, as the majority of so-far published studies, including meta-analyses, reported very low rates (0.0–1.9%) of ticagrelor HTPR ( Table 3 ) on long-term therapy [ 49 , 52 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. This prevalence practically limits the occurrence of ticagrelor HTPR to occasional clinical cases.…”
Section: Ticagrelor Resistance In Patients With Acsmentioning
confidence: 99%
“…Что касается частоты встречаемости ВОРТ при приеме ингибиторов рецепторов P2RY12 тромбоцитов, то она зависит от вида назначаемого лекарственного средства. При назначении тикагрелора и прасугрела она встречается в 0-3% и 3-15% соответственно [5,16,17]. При назначении клопидогрела частота его низкой эффективности у пациентов с ОКС исходно была от 29,5% [18] до 40,7% [19], что даже несколько выше по сравнению с нашими данными (24,5%).…”
Section: таблица 2 частота встречаемости высокой остаточной реактивно...unclassified